PEACEFUL CAMPAIGN IN ELECTION AL-HUJURAT VERSE 11 PERSPECTIVE - Doli Witro (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
Democracy is a government of the people, by the people and for the people. The popularity of the democratic system is arguably at its peak. This is proven by the many uses of the democratic system in modern countries in the world. Indonesia as a country that runs a democratic system does not give authority to the authorities to monopolize votes in an election. Because security and freedom for every citizen, free to choose as a representation of the sovereignty of the people. But on the side that democracy often happens is seen as freedom so that there are some elements mixing elements in democracy that actually damage democracy itself. Call it when campaigning for a candidate to hate speech, insult, and berate other candidates so that damage the good name in the eyes of the community. As reported in Detik.com in 2016, the National Police stated that there were 2,018 cases of hate speech that occurred. Then it increased by 44.99% in 2017 to 3,325 cases. Furthermore, in 2018 reported in January 2019 there were 3,884 cases of hate speech that occurred. This proves that in campaigning the candidates cannot be said to campaign peacefully, fairly and competitively. Whereas Allah s.w.t. It has been said in Surah al-Hujurat verse 11. Based on the description above the writer is interested in discussing and studying more about the campaign in the Elections in Indonesia and campaigning peacefully perspective of Surah al-Hujurat verse 11. This is important to discuss given the rampant hate speech cases that conducted by candidates in campaigning. This study aims to contribute knowledge to the candidates so that in campaigning, they do not utter hate speech, insult, and berate other candidates.